C37 CONCOMITANT PARTIAL PERICARDIAL AGENESIS, PERICARDIAL CYST AND POSTERIOR MITRAL VALVE LEAFLET HYPOPLASIA: A CASE REPORT. (18th May 2022) - Bianchi, N; Fabbri, G; Passarini, G; Tonet, E; Guardigli, G; Campo, G; Pavasini, R
Abstract: Background: Pericardial agenesis (1) is a congenital developmental disorder of the pleuro–pericardial membranes that is usually asymptomatic. A pericardial cyst (2) is a congenital cyst composed of mesothelial cells originating most often from the right pericardium. Hypoplasia of the posterior mitral leaflet (3) is congenital and it is very rarely diagnosed in adulthood. These alterations are usually sporadic and not associated. Case presentation: A 53–year–old woman with obesity and bronchial asthma was referred to the emergency department for left hemiparesis and concomitant dyspnoea in new–onset atrial fibrillation. A right frontal ischemic stroke was diagnosed. During the hospitalization transthoracic echocardiography was performed showing a large prolapsed anterior mitral leaflet (AML) with an eccentric and significant regurgitation. Transesophageal echocardiography was performed. It confirmed the severity of mitral regurgitation, due to a large AML prolapse, but also showed a severely hypoplastic posterior leaflet (PML). Swinging motion was also reported in the absence of pericardial effusion. In the past the patient was surgically treated for an anterior pericardial cyst that was excised. Old CT images were reviewed and showed the absence of pericardial sheets along posterior and lateral left ventricle walls, which were not contiguous to the cyst (that was anterior). The patient was finally candidated to surgery for mitral valve replacement. Discussion: The case report shows a unique case of association between partial pericardial agenesis, pericardial cyst, severe PML hypoplasia with AML prolapse and severe mitral regurgitation. The association of these three anomalies has never been described before. This could indicate a common pathogenetic denominator and therefore the need to look for this combination of structural abnormalities in carriers of even just one of them. Bibliography 1. Lopez D. et al, doi: 10.1016/j.pcad.2016.12.002 2. Khayata M. et al, doi: 10.1007/s11886–019–1153–5 3. Parato VM. et al, doi: 10.4103/jcecho.jcecho_73_17